Kepadatan dan Tempat Potensial Perindukan Larva Aedes spp. di Tempat-tempat Umum di Kecamatan Mijen Kota Semarang - Agnes Ajeung Dheandri; Sri Yuliawati; Retno Hestiningsih; Martini Martini; Siswi Jayanti (Jurnal Riset Kesehatan Masyarakat, 2021)
Semarang city is one of the endemic areas of DHF disease in Central Java Province. Mijen District is the endemic area of DHF in Semarang City, with a spike in cases in 2020. One of the potential places of transmission of DHF is public places where people gather from various regions, so this place is at high risk of DHF transmission. The purpose of this study was to find out the density and potential place of the Aedes sp larvae. in public places Mijen District semarang city. The method used is observational analytics with cross sectional research design. The larva survey method uses the single larva method. The sample of this study is 100 public places. The results of this study were mostly larvae found to be Aedes aegypti 30 (55.6%) and Aedes albopictus 24 (44.4%), the type of public places most larvae found was restaurant and bus station. Density of larvae Aedes sp. based on HI 54%, CI 26.47%, BI 63% so that density figure is in category 6-9 which means that the density of larvae is classified as high with a high risk of transmission of DHF disease caused by vectors. The larva-free index of 46% shows that it is still well below the national standard of ≥95%. The density of mosquito larvae should be controlled by conducting regular larval inspection by the janitor at the pulic places.